PENGARUH WAKTU DAN JENIS ABSORBEN PADA PROSES ENFLEURASIBUNGA MELATI (Jasminum Sambac) - Muliasari Kurniati Muchtar; Fitrika Dwi Hanani; Diyono Ikhsan (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2013)
Jasmine oil is an oil produced from the flowers jasmine (Jasmine Sambac). In this study, using the methods enfleurage and vacuum distillation. The purpose of this experiment is taking jasmine oil enfleurasi method, Assessing the impact of type of adsorbent used in the process enfleurasi and Assessing the impact of time on the enfleurasi. Benefits of this experiment was to determine the type of good absorben and optimal time enfleurasi process to obtain a high yield. Jasmine oil is known as one of the allround flavouring agent because it has a distinctive aroma, attractive and widely used in the cosmetic industry for perfumes such as soaps, perfumes. In this study there are two kinds of variables, that is remain variable and changed variable. For remain variables consist of: distillation 0.5 atm pressure, temperature 50oC, and a distillation time of 3 hours. For changed variable include the time of enfleurage 2, 4, 6, 8, 10, 12, 14, 16, 18, 20 day and type of absorbent form of petroleum jelly and beef tallow. Jasmine is obtained from Pemalang, Central Java. The observations made are the the determination, organoleptic testing, refractive index and density of jasmine oil. The results of this study, for the absorbent vaseline the highest yield of 2.07% at 20 days and enfleurasi time for absorbent beef tallowproduce the highest yield of 1.9956% at the time of enfleurasi 20 days. According organoleptic color of jasmine oil is yellow and distinctive smell of jasmine. Density obtained ranged from 0.835 ml / g to 0.915 ml / g. Refractive index obtained from the study ranged between 1.462 to 1.482.